2014
DOI: 10.9790/2402-08220513
|View full text |Cite
|
Sign up to set email alerts
|

Some trace metals content of atmospheric dusts deposition in Katima Mulilo metropolis, Namibia

Abstract: Trace metals content of atmospheric dusts continue to attract global attention as more anthropogenic activities including urban road construction impacted on the natural metals load of airborne particulates. This study employed analytical procedures to investigate the concentrations of arsenic, cadmium, cobalt, chromium, copper, nickel, lead, vanadium, tin and manganese in atmospheric dusts deposition in Katima Mulilo metropolis, Namibia. Replicate samples were collected on five days interval under dry winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The pre-treatment and digestion of collected dry atmospheric deposits have been developed according to U.S. EPA. [52] method 3050B for Inductively Coupled Plasma-Optical Emission Spectrophometer (ICP-OES) analysis cited by several authors including Abah et al [53] and Sobhanardakani [26]. A specific amount of 1.00 g of each filtered sample has been transferred into a digestion vessel, where 10 ml of 1:1 nitric acid (HNO 3 ) has been added, mixed thoroughly and covered with a watch glass.…”
Section: Sampling and Samples Analysismentioning
confidence: 99%
“…The pre-treatment and digestion of collected dry atmospheric deposits have been developed according to U.S. EPA. [52] method 3050B for Inductively Coupled Plasma-Optical Emission Spectrophometer (ICP-OES) analysis cited by several authors including Abah et al [53] and Sobhanardakani [26]. A specific amount of 1.00 g of each filtered sample has been transferred into a digestion vessel, where 10 ml of 1:1 nitric acid (HNO 3 ) has been added, mixed thoroughly and covered with a watch glass.…”
Section: Sampling and Samples Analysismentioning
confidence: 99%
“…In another study, some heavy metal concentrations in falling dust were measured in eastern Mazowieckie Province, Poland (25). Abah et al (2014) reported some trace metal content in atmospheric dust deposition in Katima Mulilo metropolis, Namibia (26). Also, Tabatabaei et al (2015) studied the geospatial patterns and background levels of heavy metals in the deposited PM in Bushehr, Iran (27).…”
Section: Introductionmentioning
confidence: 99%